PELATIHAN PENGGUNAAN SISTEM INFORMASI POSYANDU MANDIRI DAN PINUNJUL (SIAYUMAJU) UNTUK KADER POSYANDU: Posyandu Cadre Training in the Use of Information Systems for Independent and Pinunjul Posyandu (SiAyuMaju) Kuningan Regency - Rio Andriyat; Yulyanto Yulyanto; Zafira Fatsya; Agris Kurniawan (Politeknik Negeri Sriwijaya, 2022)
Information systems can be interpreted as media that can be used for the dissemination of information quickly and accurately to support the smooth operation of the organization's operations and decision making. Posyandu in Kuningan district numbered 1191 posyandu from 376 villages in 32 sub-districts in the city of Kuningan, West Java, in 2021 already implemented information technology in recording maternal and child health. The information system is a medium that can be used for the dissemination of information quickly and accurately to support the smooth operation of the organization's operations and decision making. In 2021, posyandu service activities will start from recording infants and toddlers, recording immunization data, and recording infant and toddler weight which can already be done through the Independent and Pinunjul Posyandu Information System (SiAyuMaju) at the address: http://siayumaju.kuningankab .go.id. In its application, there are problems that make the SiAyuMaju application less than optimal due to several Human Resources (HR) / Posyandu cadres who still do not have competence in mastering and using information and communication technology. This is an obstacle in operating the SiAyuMaju system which is not yet fully optimal. Based on these problems, it is necessary to train posyandu cadres in the use of the Mandiri and Pinunjul (SiAyuMaju) information systems in Kuningan Regency. Keywords: Information System, Posyandu, SiAyuMaju.